Measuring maternal, foetal and neonatal mortality: Challenges and solutions. (October 2016) - Blencowe, Hannah; Calvert, PhD, Clara; Lawn, Joy E.; Cousens, Simon; Campbell, Oona M.R.
Abstract : Levels and causes of mortality in mothers and babies are intrinsically linked, occurring at the same time and often to the same mother–baby dyad, although mortality rates are substantially higher in babies. Measuring levels, trends and causes of maternal, neonatal and foetal mortality are important for understanding priority areas for interventions and tracking the success of interventions at the global, national, regional and local level. However, there are many measurement challenges. This paper provides an overview of the definitions and indicators for measuring mortality in pregnant and post-partum women (maternal and pregnancy-related mortality) and their babies (foetal and neonatal mortality). We then discuss current issues in the measurement of the levels and causes of maternal, foetal and neonatal mortality, and present options for improving measurement of these outcomes. Finally, we illustrate some important uses of mortality data, including for the development of models to estimate mortality rates at the global and national level and for audits. Highlights: Levels and causes of mortality in mothers and babies are intrinsically linked. Measuring levels, trends and causes of maternal, neonatal and foetal mortality are interventions and track their success. There are standard definitions and indicators of measuring mortality in pregnant and post-partum women and their babies. Measurement challenges exist, awareness and attention to these would improve the measurement for these outcomes.